Pengaruh Penerapan Virtual Laboratory Berbantuan LKPD dalam Model Discovery Learning Terhadap Kompetensi Fisika Siswa - Sumi Sahara; Ramli Ramli; Zulhendri kamus (PILLAR OF PHYSICS EDUCATION, 2018)
Laboratory activities as a means of supporting physics learning are often limited by several things such as time constraints, security, the availability of tools and abstract subject matter. Kinetic Gas theory is one of the concept of physics that is abstract. One of the media that can be used to visualize abstract physics subject matter is virtual laboratory. The purpose of research is to determine the effect of the use of Virtual laboratory assisted LKPD in Discovery learning model to the achievement of physics competence of students of grade XI SMA Negeri 5 Padang. The type of research used is quasi experiment with posttest only control group design. The population in research is all students of grade XI SMA Negeri 5 Padang academic year 2017/2018. The sampling technique used is purposive sampling technique. Based on data analysis, for there are three result of research : 1) the average value of physics learning result in attitude competence has continuous improvement, 2) the average value of learning result physics in both grade samples 79.44 and 73.99 for knowledge competence; 3) average physics learning outcomes in both sample gradees 85.45 and 81.58 for skill competencies. From t test, thitung> ttable is obtained so that alternative hypothesis is accepted for knowledge competence, while for skill competence from t test, it is obtained thitung> ttable so that alternative hypothesis is accepted.